Comparative Study of Cold Sintering Process and Autoclave Thermo-Vapor Treatment on a ZnO Sample - Yurii Ivakin; Andrey Smirnov; Anastasia Kholodkova; Alexander Vasin; Mikhail Kormilicin; Maxim Kornyushin; Vladimir Stolyarov (Crystals, 2021)
Analysis of scanning electron microscopy images was used to study the changes in the crystal size distribution of ZnO, which occurred during its processing in an aqueous medium at 220–255 °C and an equilibrium vapor pressure in an autoclave. The results were compared with those of ZnO placed in a die for treatment under similar conditions supplemented with mechanical pressure application in the cold sintering process. In both cases, ZnO was treated in the presence of an activating additive: either zinc acetate or ammonium chloride. During autoclaving, a powder consisting of fine ZnO monocrystals was obtained, while the cold sintering process led to ceramics formation. Under vapor pressure and mechanical pressure, the aqueous medium affected ZnO transformation by the same mechanism of solid-phase mobility activation due to the additives’ influence. The higher the content of additives in the medium, and the higher the mechanical pressure, the more pronounced activating effect was observed. Mass transfer during the cold sintering process occurred mainly by the coalescence of crystals, while without mechanical pressure, the predominance of surface spreading was revealed. In the initial ZnO powder, the average crystal size was 0.193 μm. It grew up to 0.316–0.386 μm in a fine-crystalline powder formed in the autoclave and to an average grain size of 0.244–0.799 μm in the ceramics, which relative density reached 0.82–0.96. A scheme explaining the influence of an aqueous medium on the solid-phase mobility of ZnO structure was proposed. It was found that the addition of 7.6 mol% ammonium chloride to the reaction medium causes the processes of compaction and grain growth similar to those observed in ZnO Cold Sintering Process with the addition of 0.925 mol% zinc acetate.